2021
DOI: 10.11646/zootaxa.5026.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Sartoriana trilobata (Alcock, 1909) (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from Assam, Northeast India, with notes on the morphology of male gonopods

Abstract: Sartoriana trilobata is a species of freshwater crab which occurs exclusively in some areas of Northeast India. Being a riverine crab, it is occasionally found in beels or other riverine wetland habitats formed by monsoon floods in the Brahmaputra basin.The earlier descriptions of this species were mostly incomplete which lacked information on the morphology of the male gonopods.Therefore including the male gonopods, all the morphological features of Sartoriana trilobata are redescribed and illustrated. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yeo and Ng (2012) identified Sartoriana trilobata and S. spinigera as two distinct species based on specimens deposited at the Zoological Survey of India in Kolkata. Chetia et al, (2021) elaborated on structural differences between their gonopods, thus validating these two species. The current study found S. spinigera bearing a single sharp anterolateral tooth and a blunt merus tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Yeo and Ng (2012) identified Sartoriana trilobata and S. spinigera as two distinct species based on specimens deposited at the Zoological Survey of India in Kolkata. Chetia et al, (2021) elaborated on structural differences between their gonopods, thus validating these two species. The current study found S. spinigera bearing a single sharp anterolateral tooth and a blunt merus tooth.…”
Section: Discussionmentioning
confidence: 99%